Cultural Resonance: Enhancing Heritage Identity of Spaces with Digital Engagement - Kurniawan, Gabriel Joshua; Soemardiono, Bambang; Novianto, Didit (Journal of Architectural Design and Urbanism, 2025)
Heritage buildings serve as vital markers of cultural identity, historical continuity, and collective memory within the urban landscape. Yet in the context of accelerating urban development, many of these sites suffer from declining relevance, physical neglect, and weakening emotional connections with contemporary communities. This study explores the potential of digital placemaking as an innovative approach to revitalize the cultural significance and public engagement of heritage buildings. By integrating digital technologies with architectural space, digital placemaking reimagines these structures as interactive, inclusive, and emotionally resonant environments that bridge past and present. Employing a qualitative research methodology, this study draws from literature reviews, site analysis, community narratives, and design conceptualization to formulate a framework that supports the transformation of underutilized heritage sites into dynamic public spaces. The research highlights the importance of memory, identity, and cultural resonance as central components of revitalization efforts, proposing a layered approach that merges physical preservation with meaningful digital engagement. The outcomes of this study offer both theoretical and practical contributions to the fields of architectural design and heritage conservation, emphasizing the need for interdisciplinary, adaptive, and community-sensitive methods. This approach ensures that heritage buildings remain relevant, accessible, and culturally valuable in contemporary urban life.